2019
DOI: 10.9744/jmk.21.1.9-20
|View full text |Cite
|
Sign up to set email alerts
|

Banking Service Orientation Model in Strategic HRM and System Dynamics Perspective

Abstract: This paper seeks to explore a model of banking service orientation in strategic human resource management and system dynamic perspective, theoretically. As a scientific effort to develop a study of strategic human resource management. So far, the relationship between elements in strategic human resource management perspective as a system is only analyzed linearly. This article is the result of a literature study. An analysis is done narratively, to answer research problems. Research finding in the form of bank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 80 publications
(114 reference statements)
1
2
0
3
Order By: Relevance
“…Konsep OCBS (Bettencourt, 1998;Bettencourt et al 2001) sebagai bentuk pengembangan dari konsep OCB (Podsakoff & MacKenzie, 1997) bernilai penting untuk digunakan utamanya di perusahaan jasa yang mengutamakan pelayanan dalam proses bisnis antara lain perbankan (Junita et al, 2019;Liao & Chuang, 2004). Dimensi OCBS meliputi indikator loyalitas, kualitas pelayanan dan partisipasi (Bettencourt, 1998;Bettencourt et al, 2001;Junita et al, 2019 (Smith, 2005). Dimensi kepemimpinan melayani menurut Dennis ( 2004) diukur dengan instrumen Servant Leadership Assesment (SLAI) yang meliputi kasih sayang, pemberdayaan, visi, kerendahan hati, dan kepercayaan.…”
Section: Kajian Teoriunclassified
See 2 more Smart Citations
“…Konsep OCBS (Bettencourt, 1998;Bettencourt et al 2001) sebagai bentuk pengembangan dari konsep OCB (Podsakoff & MacKenzie, 1997) bernilai penting untuk digunakan utamanya di perusahaan jasa yang mengutamakan pelayanan dalam proses bisnis antara lain perbankan (Junita et al, 2019;Liao & Chuang, 2004). Dimensi OCBS meliputi indikator loyalitas, kualitas pelayanan dan partisipasi (Bettencourt, 1998;Bettencourt et al, 2001;Junita et al, 2019 (Smith, 2005). Dimensi kepemimpinan melayani menurut Dennis ( 2004) diukur dengan instrumen Servant Leadership Assesment (SLAI) yang meliputi kasih sayang, pemberdayaan, visi, kerendahan hati, dan kepercayaan.…”
Section: Kajian Teoriunclassified
“…Variabel moderasi dalam penelitian ini adalah gender. Variabel dependen adalah Organizational Ctizenship Behavior (OCB) yang diukur dengan tiga dimensi OCB berorientasi pelayanan (Service-Oriented OCB/ OCBS) (Bettencourt, 1998;Bettencourt et al, 2001;Junita et al, 2019).…”
Section: Pengaruh Kepemimpinan Melayani Terhadap Perilaku Ocb Dengan unclassified
See 1 more Smart Citation
“…When employees identify themselves with the organization, they will feel bound as members of the organization. Aisyah and Wartini (2016) and Junita et al (2019) even confirmed that organizational commitment is a critical mediating variable that connects various organizational predictors to raise an employee's OCB.…”
Section: Introductionmentioning
confidence: 93%
“…Another individual predictor that contributes significantly to the emergence of employee OCB is organizational commitment. The previous research results have proven that organizational commitment is a strong predictor of the emergence of OCB in employees (Aisyah & Wartini, 2016;Wijaya & Yuniawan, 2017;Pigome et al, 2019;Junita, 2017;Junita et al, 2019;Busharmaidi, 2020). In this case, commitment is an affective aspect that influences an individual's work behavior (McShane & Von Glinow, 2010).…”
Section: Introductionmentioning
confidence: 96%